Understanding the Influence of Teacher-Directed Scientific Inquiry on Students' Primal Inquiries in Two American Science Classrooms. Issue 4 (1st October 2020) - Stone, Brian
ABSTRACT: Scientific inquiry is an often misunderstood concept in many elementary classrooms. On the inquiry spectrum, teacher-directed (TD) scientific inquiry is prevalent in schools. From a critical and social constructivism framework, TD inquiry programs affect students' original/unhindered questions, called primal inquiry (PI), and processes in science as well as classroom climate factors, such as engagement, interest, and motivation. For this case study, two 4th-grade elementary science classrooms were observed for a total of 23 hours, and 22 students were interviewed. The classroom climate was described in relationship to TD inquiry and its influence on the students' own inquiries (PI). Classroom observations, field notes, student interviews, and science journals were analyzed for any impact of TD instruction on students' own inquiries (PI). Overall, three major effects were observed: multiple and substantial barriers to authentic student inquiry existed, students' original questions were rarely engaged or revisited in the classroom (inelasticity), and climate factors (engagement, interest, and motivation) were negatively affected in relation to TD inquiry events.